Multiscale Fracturing in Medium- to Low-Rank Coals and Its Implications on Coalbed Methane Production in the Baode Area, Eastern Ordos Basin, China - Wei Zhang; Baoshan Zhao; Qingfeng Zhang; Jikun Zhang; Ziling Li; Xiaoguang Sun; Mingming Yan (Geofluids)
Coal fractures are crucial in affecting the production of methane from coal. Multiscale fracturing and its implications on coalbed methane production have still not been fully understood. Herein, we present a case study, combining underground coal mine surveying and specimen, thin section, and scanning electron microscope observations for illustrating the ~m-, ~cm-, ~mm-, and ~μm-scale fractures present in the Baode area, eastern Ordos Basin, China. Then, the fracture connectivity is evaluated by helium permeability and mercury porosimetry measurement. The coals are mainly of semibright, semidull, and dull macrolithotypes. And main maceral composition is vitrinite, accounting for 73%~95%, with around 26% inertinite. The coals are ultralow-ash and low-ash content, belonging to high-volatile bituminous coal. The ~m scale fractures can penetrate the whole coal seams, dominant by S-N and following E-W direction, which were generated during the Yanshanian and Himalayan movements. The ~cm fractures are generally parallel to the lamina, influenced by the bright and dull coal band extension caused by the depositional differences. The ~mm fractures are mainly shown as endogenous fractures perpendicular to the lamina restricted within bright macrolithotypes. There are also ~mm fractures that are perpendicular to the lamina while penetrating dull components and fractures parallel to the lamina. The ~μm fractures are widely distributed and connect each other. Some of the fractures are filled with carbonate and clay minerals and are beneficial for methane migration, caused by hydraulic fracturing. The average mercury withdrawal efficiency of the coals was 75%. The helium permeability of the coals was between 10×10−3 and 50×10−3 μm2, indicating good fracture connectivity. The study findings, which indicated the presence of fractures of different scales in the coals studied, can be used for fully understanding the coalbed methane performance of medium- and low-rank coals.